Sikap Emosional Ketika Menghadapi Krisis - Peter, Ramot (Humaniora, 2014)
Crisis is part of life that cannot be avoided but must be overcome. A crisis tends to cause problems and will have an impact on emotional attitude that should be taken. Most people face a crisis with a negative attitude because they consider the presence of crisis as obstacle in life. Negative emotional attitude will bring people to action breakout, even worse, actions that will make life more miserable. In accordance with the will of God, we are expected to overcome the crisis, though it is a barrier in life, with a positive emotional attitude supported by the spiritual attitude so that the crisis has positive impact. Spiritual attitude shows that someone who understands God's word and will for sure be able to resolve the problem, find a way out or strength to face the crisis. So, the crisis is not the bottleneck of life but a turning point towards improvement that gives goodness.